Consequences of Delayed Maintenance of Highway Assets - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 859: Consequences of Delayed Maintenance of Highway Assets presents a process for quantifying the consequences of delayed maintenance of highway assets that considers the asset preservation policy, the maintenance and budget needs, and the analyses of delayed maintenance scenarios. This process considers delayed maintenance caused by the inability to meet the agency-defined application schedule or the unavailability of the funds required to perform all needed maintenance, and expresses the consequences in terms of asset condition and the costs to owners and road users. Detailed descriptions of the use of the proposed process to quantify the consequences of delayed maintenance for seven highway assets are available in appendices from the contractor’s final report:Appendix C-PavementsAppendix D-BridgesAppendix E-CulvertsAppendix F-GuardrailsAppendix G-LightingAppendix H-Pavement markingsAppendix I-Signs
Keywords: Transportation and Infrastructure

Interactions Between Transportation Capacity, Economic Systems, and Land Use - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-C03-RR-1: Interactions Between Transportation Capacity, Economic Systems, and Land Use provides information on the development of a large database of case studies and a web-based T-PICS (Transportation Project Impact Case Studies) tool that allow for more rapid assessment of the long-term economic impacts of highway capacity projects.SHRP 2 Report S2-C03-RR-1 and the accompanying T-PICS web-based tool are intended to serve as a resource for transportation planners and others who are interested in better understanding the long-term economic impacts of highway capacity projects. The T-PICS web-based tool provides transportation planners with a way to search for relevant case studies by type of project and setting. The case studies include details of the projects, their impacts, and factors affecting the impacts. The web tool also provides users with an option to specify the type of proposed project and see the range of likely impacts based on the studies.SHRP 2 Capacity Project C03 also developed three additional related materials: a data dictionary, a users guide, and performance metrics.SHRP 2 Report S2-C03-RR-1 includes an explanation of how the case studies were selected and developed, an introduction to T-PICS, and a meta-analysis of the key relationships among factors such as project type, traffic volume, project location, and nontransportation policies aimed at fostering economic development.An e-book version of this report is available for purchase at Google, iTunes, and Amazon.Errata: Figure 4.3 (p. 23) was cut off along the right edge and did not display all of the information in the bar graph. The figure has been corrected in the electronic version of the report.Disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Using the Economic Value Created by Transportation to Fund Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 459: Using the Economic Value Created by Transportation to Fund Transportation presents information on financing mechanisms used by transportation agencies to capture a portion of the economic value created by public investment in transportation infrastructure to fund transportation improvements.The report provides an overview of ten types of “value capture” mechanisms and presents case examples of how transportation agencies have used these mechanisms to help fund specific highway projects.
Keywords: Transportation and Infrastructure

Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB Special Report 329: Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future explores pending and future federal investment and policy decisions concerning the federal Interstate Highway System. Congress asked the committee to make recommendations on the “features, standards, capacity needs, application of technologies, and intergovernmental roles to upgrade the Interstate System” and to advise on any changes in law and resources required to further the recommended actions. The report of the study committee suggests a path forward to meet the growing and shifting demands of the 21st century.The prospect of an aging and worn Interstate System that operates unreliably is concerning in the face of a vehicle fleet that continues to transform as the 21st century progresses and the vulnerabilities due to climate change place new demands on the country’s transportation infrastructure. Recent combined state and federal capital spending on the Interstates has been about $20–$25 billion per year. The estimates in this study suggest this level of spending is too low and that $45–$70 billion annually over the next 20 years will be needed to undertake the long-deferred rebuilding of pavements and bridges and to accommodate and manage growing user demand. This estimated investment is incomplete because it omits the spending that will be required to meet other challenges such as boosting the system’s resilience and expanding its geographic coverage.The committee recommends that Congress legislate an Interstate Highway System Renewal and Modernization Program (RAMP). This program should focus on reconstructing deteriorated pavements, including their foundations, and bridge infrastructure; adding physical capacity and operations and demand management capabilities where needed; and increasing the system’s resilience. The report explores ways to pay for this program, including lifting the ban on tolling of existing general-purpose Interstate highways and increasing the federal fuel tax to a level commensurate with the federal share of the required RAMP investment.View the videos, recorded webcast, graphics, summary booklet, press release, and highlights page at interstate.trb.org.
Keywords: Transportation and Infrastructure

Best-Value Procurement Methods for Highway Construction Projects - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 561: Best-Value Procurement Methods for Highway Construction Projects examines procurement methods, award algorithms, and rating systems for use in awarding best-value highway construction contracts. The report also explores screening criteria for selecting projects for application of best-value procurement, implementation strategies, and a model best-value specification.
Keywords: Transportation and Infrastructure

Life-Cycle Cost Analysis for Management of Highway Assets - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 494: Life-Cycle Cost Analysis for Management of Highway Assets documents the state of the practice of life-cycle cost analysis (LCCA) and risk-based analysis into state highway agencies' asset management plans for pavements and bridges on the National Highway System. The objective of this project was to develop an inventory of quantitative asset-level, project-level, or corridor-level processes and models for predicting life-cycle costs associated with the preservation and replacement of highway assets. The report includes a literature review, a survey of highway agencies, and case studies that document specific highway agency experiences with LCCA.
Keywords: Transportation and Infrastructure

Practices for Establishing Contract Completion Dates for Highway Projects - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 502: Practices for Establishing Contract Completion Dates for Highway Projects documents current methodologies and procedures used by state transportation agencies to estimate contract time for various highway project delivery methods. Establishing contract time is an important part of the highway project development process because it directly impacts project costs, the public, and risk for contractors.
Keywords: Transportation and Infrastructure

Effective Project Scoping Practices to Improve On-Time and On-Budget Delivery of Highway Projects - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 821: Effective Project Scoping Practices to Improve On-Time and On-Budget Delivery of Highway Projects demonstrates how a state department of transportation (state DOT) can enhance its scoping process and practices to produce a project cost estimate and schedule that facilitate improved programming decision making and accountability. The guidebook illustrates the effort needed to develop a robust cost estimate and then manage to a baseline budget and scope throughout the project delivery cycle. The guidebook is applicable to a range of project types and is scalable in its ability to accommodate projects of varying complexity.Increasing or otherwise changing the scope of a project to improve facility performance is a common source of cost increases and schedule delays, as is failure to adequately consider project impacts on utilities, communities, or the environment. Industrial and commercial building construction sectors have experienced similar problems with construction project scope growth, cost increases, and time delays that occur after a project has been authorized for detailed design and construction.Recent research in these sectors has produced a structured and systematic process to help owners meet project cost and schedule objectives by defining a project to a suitable level of development prior to authorization of detailed design. Statistical evidence indicates that earlier and more detailed scoping efforts can reduce total design and construction cost by as much as 20%, and shorten total design and construction schedules by as much as 39%. Such scoping processes, with supporting indices and tools to calibrate the level of scoping effort required to achieve these results, have become standard procedures that many private U.S. corporations use in their capital facilities development efforts. With modifications, these processes and tools may be transferable to the transportation industry.
Keywords: Transportation and Infrastructure

Final Report for NCHRP Report 574: Guidance for Cost Estimation and Management for Highway Projects During Planning, Programming, and Preconstruction - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 98, Final Report for NCHRP Report 574: Guidance for Cost Estimation and Management for Highway Projects during Planning, Programming, and Preconstruction details the steps followed by the research team in the development of NCHRP Report 574: Guidance for Cost Estimation and Management for Highway Projects during Planning, Programming, and Preconstruction. NCHRP Report 574 examines highway cost estimation practice and cost estimation management with the goal of helping achieve greater consistency and accuracy between planning, programming and preliminary design, and final design. The Guidebook explores strategies, methods, and tools to develop, track, and document realistic cost estimates during each phase of the process.
Keywords: Transportation and Infrastructure

Techniques for Effective Highway Construction Projects in Congested Urban Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 413: Techniques for Effective Highway Construction Projects in Congested Urban Areas explores a diverse set of techniques designed to address highway construction challenges in congested urban areas such as high-traffic volumes, utility conflicts, complex right-of-way acquisition issues, a diverse stakeholder base, and watchful news media.The report includes four case studies designed to help illustrate effective construction practices in congested urban areas.
Keywords: Transportation and Infrastructure